ANALISIS FAKTOR SIKAP PADA PERILAKU PENCEGAHAN PENULARAN HIV/AIDS PADA IBU HAMIL - Romdiyah, Romdiyah; Alviana, Fifi (Jurnal Ilmiah Kesehatan, 2020)
Purpose: To analyze the attitude factor on the prevention of HIV / AIDS transmission in pregnant women. Methods: The design of this study was non-experimental (observational) with a cross sectional design. The sampling technique used total sampling or saturated sampling with a total of 60 pregnant women. The analysis used univariate, biavariate and multivariate analysis. Results: The proportion of respondents in prevention behavior is more in the group that has an attitude about preventing transmission of HIV / AIDS that is less supportive (70.0%) compared to the group that has an attitude about preventing transmission of HIV / AIDS that supports (30.0%). Chi square analysis test results obtained p = 0.003. Conclusion: There were a relationship between attitudes towards preventing transmission of HIV / AIDS with behaviors to prevent transmission of HIV / AIDS. Key word: Attitudes, HIV / AIDS, pregnant women